Student outcomes, learning environment, logical thinking and motivation among computing students in an Indonesian university. - Soerjaningsih, Widia (Curtin University, 2001)
This study involved examining differences and similarities between the learning environment perceptions of students attending the Computer Science department and the Management department at an information technology university in Jakarta, Indonesia. In doing so, the study investigated which types of learning environments were most likely to strengthen student outcomes in computer-related courses and identify ways in which the university could enhance the teaching and learning process.The study examined whether relationships exist between students' cognitive and affective outcomes and four productivity factors: the learning environment; the quality of teacher-student interactions; students' aptitude; and students' motivation to select their chosen subject. To measure the four productivity factors, 422 students from 12 classes were asked to respond to four questionnaires that were modified to suit tertiary-level computing students: (1) the What is Happening in this Class? questionnaire (WIHIC) to measure students' perceptions of the learning environment, (2) the Questionnaire on Teacher Interaction (QTI) to measure students' perceptions of the student-teacher interaction; (3) the Test of Logical Thinking (TOLT) to measure the students' aptitude; and (4) a scale that was developed to measure students' motivation towards their course. To measure students' cognitive outcomes, information was retrieved from the university database and, to measure students' attitudes towards their computer-related subjects, four modified scales from the Test of Science Related Attitudes (TOSRA) were used.Each of the instruments was found to be valid and reliable in the Indonesian language for use at the university level in terms of factor structure, internal consistency reliability, and ability to differentiate between the perceptions of students in different classrooms. These instruments provide a, means by which lecturers can monitor their classroom environments, their lecturer interaction behaviour and their students' logical thinking, motivation and attitudes. Generally, it was found that computer science students perceived the classroom environments more favourably than management students. These findings related to departmental differences at the university level provide insights into how students from different departments perceive the learning environment. Also, the study pointed to departmental differences in students' logical thinking which could influence the types of learning environment that suit students from different departments. Departmental differences in students' perceptions of the lecturer-student interpersonal behaviour suggest that lecturers should take note that the personal relationships which they build and the ways in which they treat students.